PENGEMBANGAN BAHAN AJAR KOMPUTERISASI AKUNTANSI BERBASIS MULTIMEDIA - Muh. Fachrul (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2010)
This Application explain about study of MYOB Accounting of where items presented contain the items of about Company Case, Setup of Early MYOB, and Beginning Balance of MYOB Accounting. This Application can give the study interaktif of at student or user of other;dissimilar so that can understand about submitted/sent items This application is developed with the concept Multimedia and exploit the program of Macromedia Authorware 6.5 as program develop. By using application program this interaktif, is expected by a student will be able to be easier in comprehending Iesson which have in learning in campus, because this multimedia own the animation and video which can add the student motivation to learn With the interesting appearance in expecting student more like to learn, because in this application is student do not only listen the clarification from just tutor but also have interaction, that is with clicking knob which have been provided. interesting appearan ce possible can lessen the student saturation in accepting Iesson. Others student also can test its ability in doing problem - problem which have been provided.